Nicotine-replacement therapy: a proven treatment for smoking cessation - Robson, Noor Zurani (Medpharm Publications, 2010)
Smoking is a major cause of cardiovascular diseases, respiratory diseases and cancer. Despite the high prevalence of smokers worldwide, smokers are often neglected and not offered effective assistance with quitting their habits. In order to overcome this public health burden, effective treatment is needed to help smokers stop smoking. Among the pharmacological treatments available, nicotine-replacement therapy (NRT), when prescribed in combination with behavioural support, has been proven to be effective in helping a wide range of smokers to quit. NRT helps smokers during the withdrawal process by replacing a proportion of the nicotine formerly obtained from cigarettes. NRT is available in many formulations. The commonly prescribed formulations are nicotine gum, nicotine patches, nicotine inhaler and nicotine nasal spray. The choice of which NRT to prescribe depends on the patient’s condition, established guidelines and protocols and availability. This article aims to review the role of NRT in smoking cessation.